Notable Individuals Named Fazlur Rahman: A Comparative Biographical Study - Wekke, Ismail Suardi (International Humanity Advance, Business & Sciences, 2025)
This comparative biographical study explores the lives and legacies of notable individuals named Fazlur Rahman, who have made significant contributions across diverse fields such as structural engineering, Islamic scholarship, religious education, political leadership, and missionary work. The study includes figures like Fazlur Rahman Khan, a pioneering structural engineer; Fazlur Rahman Malik, a leading Islamic modernist thinker; Moulana Fazlur Rahman, a traditional scholar and spiritual guide; Fazal-ur-Rehman, a prominent Pakistani politician; and Dr. Muhammad Fazlur Rahman Ansari, an influential theologian and missionary. By examining their biographies, intellectual outputs, and socio-political impacts, the paper highlights both the unique paths and common themes of excellence and leadership these individuals represent. The inclusion of a controversial figure, Fazlur Rahman Khalil, underscores the diversity of legacy among individuals sharing the same name. This study contributes to the understanding of how shared identities can traverse vastly different trajectories, offering insight into cultural, religious, academic, and political landscapes across regions.